Sensing behavior of acetone vapors on TiO₂ nanostructures — application of density functional theory - Nagarajan, V.; Sriram, S.; Chandiramouli, R. (Condensed Matter Physics, 2017)
The electronic properties of TiO₂ nanostructure are explored using density functional theory. The adsorption properties of acetone on TiO₂ nanostructure are studied in terms of adsorption energy, average energy gap variation and Mulliken charge transfer. The density of states spectrum and the band structure clearly reveals the adsorption of acetone on TiO₂ nanostructures. The variation in the energy gap and changes in the density of charge are observed upon adsorption of acetone on n-type TiO₂ base material. The results of DOS spectrum reveal that the transfer of electrons takes place between acetone vapor and TiO₂ base material. The findings show that the adsorption property of acetone is more favorable on TiO₂ nanostructure. Suitable adsorption sites of acetone on TiO₂ nanostructure are identified at atomistic level. From the results, it is confirmed that TiO₂ nanostructure can be efficiently utilized as a sensing element for the detection of acetone vapor in a mixed environment. Дослiджуються електроннi властивостi TiO₂ наноструктури з використанням теорiї функцiоналу густини. Властивостi адсорбцiї ацетону на TiO₂наноструктурi вивчаються в термiнах енергiї адсорбцiї, змiни середньої енергiї щiлини i переносу заряду Муллiкена. Спектр густини станiв та структура зони чiтко вказують на адсорбцiю ацетону на TiO₂ наноструктурах. Змiна енергiї щiлини та змiни густини заряду спостерiгаються пiсля адсорбцiї ацетону на базовому матерiалi TiO₂ n-типу. Результати спектру густини станiв показують, що перенос електронiв вiдбувається мiж парою ацетону i TiO₂ базовим матерiалом. Отриманi данi показують, що властивостi адсорбцiї ацетону є бiльш сприятливими на TiO₂ наноструктурi. Зручнi мiсця для адсорбцiї ацетону на TiO₂ наноструктурi iдентифiкуються на атомарному рiвнi. Згiдно з отриманими результатами, пiдтверджується, що TiO₂ наноструктуру можна ефективно використовувати в якостi чутливого елемента для виявлення випарiв ацетону у змiшаному довкiллi.